Chinese shadow theatre : history, popular religion, and women warriors - Chen, Fan-Pen Li, 1953- (McGill-Queen's University Press, 2007)
In her study of Chinese shadow theatre Fan Pen Li Chen documents and corrects misconceptions about this once-popular art form. Drawing on extensive research and fieldwork, she argues that these plays served a mainly religious function during the Qing dynasty and that the appeal of women warrior characters reflected the lower classes' high tolerance for the unorthodox and subversive.